REMEDIASI MISKONSEPSI MATERI FLUIDA STATIS MENGGUNAKAN METODE EKSPERIMEN DI MAN 2 FILIAL PONTIANAK - Sasmiati, Sri; Tandililing, Edy; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstrak: This study aimed to determine the effectiviness of Experiment Method to remediate misconceptions in fluid statics at MAN 2 Filial Pontianak. The method used is Pre Experimental Design with One Group pretest post test design. Data taken from the students of class XI IPA selected intact group. The sample was 30 students. Data collection tool in the form of 18 multiple choice questions with three alternative answers and the reasons open. Based on the analysis of data obtained The average percentage decrease in number of students who have misconceptions of 43.7%. Based on McNemar test calculations obtained an average Ï‡2Compute () ËƒÏ‡2Table (3.84) for db = 1 and Î± = 5%, then the overall conception significant changes after remediated usingÂ experiment method. DQM effectiveness calculations obtained 71,71% (high category), the remediation using experiment method effective in addressing misconceptions learners.Â Keywords: Misconception, Remediation, Â Experiment Method, Fluid Statics.